Mechanism of BDNF Modulation in GABAergic Synaptic Transmission in Healthy and Disease Brains - Porcher, Christophe; Medina, Igor; Gaiarsa, Jean-Luc (Frontiers in Cellular Neuroscience, 2018)
In the mature healthy mammalian neuronal networks, γ-aminobutyric acid (GABA) mediates synaptic inhibition by acting on GABAA and GABAB receptors (GABAAR, GABABR). In immature networks and during numerous pathological conditions the strength of GABAergic synaptic inhibition is much less pronounced. In these neurons the activation of GABAAR produces paradoxical depolarizing action that favors neuronal network excitation. The depolarizing action of GABAAR is a consequence of deregulated chloride ion homeostasis. In addition to depolarizing action of GABAAR, the GABABR mediated inhibition is also less efficient. One of the key molecules regulating the GABAergic synaptic transmission is the Brain Derived Neurotrophic Factor (BDNF). BDNF and its precursor proBDNF, can be released in an activity-dependent manner. Mature BDNF operates via its cognate receptors tropomyosin related kinase B (TrkB) whereas proBDNF binds the p75 neurotrophin receptor (p75NTR). In this review we discuss recent finding illuminating how mBDNF-TrkB and proBDNF-p75NTR signaling pathways regulate GABA related neurotransmission under physiological conditions and during epilepsy.